Al2O3 micro- and nanostructures affect vascular cell response. Issue 21 (11th February 2016) - Kiefer, Karin; Akpınar, Gürler; Haidar, Ayman; Ikier, Tuba; Akkan, Cağrı Kaan; Akman, Erhan; Lee, Juseok; Miró, Marina Martinez; Kaçar, Elif; Demir, Arif; Veith, Michael; Ural, Dilek; et al.
Abstract : Novel nano- and microstructured surfaces are fabricated for cardiovascular implant application. A topography driven selective cell response of ECs over SMCs was demonstrated successfully. Abstract : In-stent restenosis (ISR) is one of the most common and serious complications observed after stent implantation. ISR is characterized by the inordinate proliferation of smooth muscle cells (SMC) that leads to narrowing of the blood vessels. To achieve a healthy endothelium, it is critical to selectively enhance the growth of endothelial cells (EC) while suppressing the growth of smooth muscle cells, which is still a major challenge and yet to be achieved. In this study, novel surfaces have been developed to support the selective growth of endothelial cells. Micro- and nanostructured Al2 O3 surfaces with unique topographical features were fabricated and tested. Surface characterization and cellular response of endothelial cells (HUVEC) as well as smooth muscle cells (HUVSMC) has been investigated at cellular and molecular levels. A topography driven selective cell response of ECs over SMCs was demonstrated successfully. This selective response of ECs was also analyzed at protein levels in order to understand the basic mechanism.